Anion-based Weather Modification Technology to Reduce Food and Forest Fire Risks (Karhutla) during Covid-19 Pandemic - Goenawan, R Djoko; Tukiyat, Tukiyat; Widodo, F Heru (Universitas Sebelas Maret, 2020)
During the dry season there was potential for forest and land fires and the water supply in the reservoir was reduced, including electricity & agriculture. An effort made by Government (1976-2020), was TMC (weather modification technology) which used aircraft and chemicals. Many roads lead to Rome, including Anion-based TMC and solar power. TMC Anion in Indonesia is still being studied, but in several countries it has entered the operational and commercial phases and can compete with the provision of clean water with other technologies. TMC studies and experiences in Australia, Oman, Jordan, as well as Germany, Switzerland and Russia. TMC is very prospect applied in Indonesia, also very economical. In addition, smoke as Karhutla particles is a problem, both visibility and ISPA disease, with TMC Anions smoke can be modified into CCN and finally into clouds and rain, so that Karhutla can be reduced and water supply can be fulfilled.